Storage of Seedlings of Three Recalcitrant Dipterocarp Species by Slow Growth Techniques - Tsan, Fui Ying (2000)
Most dipterocarp species are erratic seed bearers and produce recalcitrant seeds. This study was designed to explore the possibility of storing their seeds as slow growing seedlings for the continuous supply of planting materials for various planting programmes. Shorea ovalis seedlings showed suspended growth while Shorea leprosula could be stored as slow growing seedlings at 150 Ilmollm2/s PPFD for twelve months. Storage at a density of 700 seedlings/m2 on the forest floor under this low radiation condition however, resulted in mortality rate of above 20% due to herbivory of cotyledons, broken branches from the trees above, damping off and intraspecific competition. Hopea odorata were free from damping off when maintained at a slow growth phase for the same length of period on the forest floor at densities of 300, 500 and 700 seedlings/m2. The other factors as mentioned, however, resulted m mortality rate of above 20% also in these seedlings.